Ciguatoxin-like toxin in mackerel Acanthocybium soladria in Vietnam - Ha, Dao Viet; Vy, Phan Bao (Vietnam Journal of Marine Science and Technology, 2019)
Two processed mackerel products were sent to VAST keylab on “Food and Environmental Safety” in Institute of Oceanography for Ciguatoxin criteria as exported seafood requirement. The specimens were caught from offshore region of Vietnam South-Eastern sea in April 2019. By DNA sequencing of COI gene, both specimens were identified as Acanthocybium solandri, one of high commercial mackerel species which is well-known to be distributed in Central and South-Eastern sea of Vietnam. In mouse bioassay, both extracts from 2 samples exhibited acute toxicity, which killed tested mice within 6 and 15 hours after i.p. injection. In SIM LC/MS-MS analysis, the extracts showed the peak with retention time closed to that in CTX-1B standard in both cases of optimized and non-optimized solid phases. The result suggested that at least there was occurrence of CTX-like toxin in these mackerel specimens. The equivalent toxin levels were estimated as 0.51 ng/g and 0.84 ng/g; 5 and 8 times higher than regulation limit for CTXs in seafood product (0.1 ng CTX-1B/g). Further verification is in progress to confirm toxin in these mackerel samples in Vietnam. However, this data is the first alert on potential poisoning by consumption of mackerel, not only in Vietnam but also in Asia